Światy wartości mieszkańców miasta. Na przykładzie badań socjologicznych w Zabrzu - Świątkiewicz, Wojciech Krzysztof (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Values belong to the cultural order and constitute the foundations of social life. By internalizing them in attitudes and behaviors, in the practices of social life, people shape the cultural profiles of both entire communities and the social personalities of individuals. Communities are created around a community of values and because of this, they take specific forms, such as nations, states, cultural regions, cities or religious communities. Cultural profiles of individuals’ social personalities are a consequence of the internalization of the world of values into individually constructed and implemented projects of social life. The article presents the reconstruction of value systems of the city’s inhabitants, based on empirical research. It focuses on material conditions of declared values orientation and the hierarchy of dignity values. In the hierarchy of recognized values, primary, dominant, indifferent, secondary and marginal values have been distinguished. Many factors: historical and contemporary, cultural and political, determine whether it models the image of the “citizen of the cit””, which is possible to reconstruct based on the conducted research. Its most visible feature is the axiological distance and maybe even the gap between primary and marginal values.